Creating research and development awareness among dental care professionals by use of strategic communication: a 12-year intervention study - Helena Morténius; Svante Twetman (BMC, 2017)
Abstract Background Despite the availability of contemporary research advances, only a limited fraction is implemented into dental practice. One possible way to facilitate this process is to stimulate the research and development (R&D) awareness and interest with aid of strategic communication. Methods The aim of the study was to analyse the role of a strategic communication in R&D awareness and interest among dental care professionals (DCP) over a 12-year period. A second aim was to compare the findings with those from primary care professionals (PCP). The project had a prospective design and the intervention was conducted through established oral, written and digital channels. The outcome was captured by two validated questionnaires submitted after 7 and 12 years, respectively. An additional Questionnaire file shows the details [see Additional file 1]. The material consisted of 599 health care professionals (205 DCP; 394 PCP) that responded to the first questionnaire and 526 individuals (195 DCP; 331 PCP) who responded to the second. All were employed by the primary care organization of Region Halland located in southwest of Sweden. The majority were women (≥ 85%) and the mean age at the first questionnaire was 49 years (SD 8.5). Longitudinal analyses were applied to those individuals that responded to both surveys after 7 and 12 years (n = 248). Comparisons between DCP's and PCP's were processed with Chi-square and Fischer's exact tests. Results Strategic communication contributed to increase the R&D awareness and interest among the dental personnel. The created interest was reported stronger among the DCP when compared with PCP at both surveys (p < 0.05). The longitudinal findings confirmed a long-term interest among the DCP's. Direct and indirect communication facilitated R&D interest in both groups. The most powerful channels were the written "Research bulletin" and peer inspiration. Conclusion Strategic communication can be employed as a scientific tool that may contribute to the creation of a long-term R&D awareness and interest among dental care professionals.